2010
DOI: 10.1162/jocn.2009.21211
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Human Body Perception

Abstract: The objective of this study was to investigate potential sex differences in the neural response to human bodies using fMRI carried out in healthy young adults. We presented human bodies in a block-design experiment to identify body-responsive regions of the brain, namely, extrastriate body area (EBA) and fusiform body area (FBA). In a separate event-related "adaptation" experiment, carried out in the same group of subjects, we presented sets of four human bodies of varying body size and shape. Varying levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 65 publications
6
41
0
Order By: Relevance
“…Recent evidence suggests that the gender of the observer may influence the lateralization of EBA response to human body images. Aleong and Paus (2010) showed that healthy women exhibited greater response to human bodies in the right vs. left EBA and greater right EBA response compared with men. The right and left hemispheres may have complimentary roles in visual body representation and their relative involvement may be different in women and men.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent evidence suggests that the gender of the observer may influence the lateralization of EBA response to human body images. Aleong and Paus (2010) showed that healthy women exhibited greater response to human bodies in the right vs. left EBA and greater right EBA response compared with men. The right and left hemispheres may have complimentary roles in visual body representation and their relative involvement may be different in women and men.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, since higher BMI values are observed in men than women, considering this confounding variable is crucial when testing gender differences in body perception. Aleong and Paus (2010) reported that men and women with higher BMI showed reduced hemispheric asymmetry in the response of EBA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that exactly the same stimuli were used for both tasks, thus suggesting that the different roles of extrastriate and premotor areas in processing body forms and body actions arise from the implicit task demands (i.e., whether the stimuli can be differentiated by form or action 13 cues) rather than from the stimulus features per se (i.e., whether the posture implies more or less motion). Furthermore, EBA activity is sensitive to subtle variation of human body size and shape in healthy individuals (Aleong & Paus, 2010) and its structural and neurofunctional alteration is associated with body image disturbance, such us body size overestimation and negative body evaluation in patients with EDs (Uher et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the design of our study had not enough power to analyze and detect gender differences in the pattern of results, but it is possible that the relative contribution of left and right hemisphere areas in the aesthetic appreciation of same and different-gender bodies may vary also according to the gender of the observer (Cazzato et al, 2014;Aleong & Paus, 2010).…”
Section: Limitations and Conclusionmentioning
confidence: 98%